Employee Challenges in Improving the Quality of Human Resources in the Era of Globalization - Arifin, Samsul; Ansori, Mochammad; Safrizal, Helmi (LPPM Institut Bisnis dan Informatika Kesatuan, 2023)
Improving the quality of human resources (HR) has become the main focus in facing the dynamics of globalization. Globalization, with all its changes, encourages the need for human resource development through out-of-school education. The background of this research involves complex challenges in economics, politics and culture that require smart and globally minded human resources. The purpose of this study is to analyze the role of non-formal education in producing competent and adaptive human resources in the face of globalization. The research method involves a descriptive and qualitative analysis approach. Data were collected through literature studies and interviews with education experts. The results show that developing human resources through out-of-school education requires a strategy that is proactive, involves community participation, and focuses on learning innovation. The success of this strategy depends on improving quality, relevance and management involving the community and local government. The research discussion highlights the importance of skills and knowledge that are relevant to the demands of the global job market. On the political side, understanding local issues in a global context is key, while on the cultural aspect, cosmopolitanism and diversity are important. Thus, non-formal education not only teaches skills, but also builds characteristics such as achievement motivation, adaptability, innovation, and resilience to change.